Peningkatan Kapasitas Kecakapan Hidup (Life Skill) Siswa SMK Telkom Kendari Melalui Pengolahan Limbah Kulit Singkong - Asriani, Asriani; Rahma Ma’mun, St. (Amaliah: Jurnal Pengabdian Masyarakat, 2017)
Nowadays, the cassava skin waste had been taken only a few advantages by people in Kendari. By increasing value-added this waste needed process to become economical product. It aims are; (1) to knowhow the processcassava wasteprocessed into chips, (2) to improveskill and entrepreneurial passion of SMKTelkomKendari students. The methods are many activitiessuch as observationsite which followingproperly materials/theoriesthat ita lectureanddiscussion which how the cassava leather are been processing. Thenthe next phase are trainingand practicing that it ended of evaluation. As a results, this activityshowedthatevent increased significantly. They had been understanding and interesting towards own business which amount at 50percent.They increase significant in knowledge tomake achipsamount90percent. This activity had improved student capability to incline their life-skills